Comprehensive Analysis of the SBP Family in Blueberry and Their Regulatory Mechanism Controlling Chlorophyll Accumulation - Xie, Xin; Yue, Shaokang; Shi, Baosheng; Li, Hongxue; Cui, Yuhai; Wang, Jingying; Yang, Pengjie; Li, Shuchun; Li, Xuyan; Bian, Shaomin (Frontiers in Plant Science, 2021)
SBP family genes act as central players to regulate plant growth and development with functional redundancy and specificity. Addressing the diversity of the SBP family in crops is of great significance to precisely utilize them to improve agronomic traits. Blueberry is an important economic berry crop. However, the SBP family has not been described in blueberry. In the present study, twenty VcSBP genes were identified through data mining against blueberry transcriptome databases. These VcSBPs could be clustered into eight groups, and the gene structures and motif compositions are divergent among the groups and similar within each group. The VcSBPs were differentially expressed in various tissues. Intriguingly, ten VcSBPs were highly expressed at green fruit stages and dramatically decreased at the onset of fruit ripening, implying that they are important regulators during early fruit development. Computational analysis showed that ten VcSBPs were targeted by miR156, and four of them were further verified by degradome sequencing. Moreover, their functional diversity was studied in Arabidopsis. Noticeably, three VcSBPs significantly increased chlorophyll accumulation, and qRT-PCR analysis indicated that VcSBP13a in Arabidopsis enhanced the expression of chlorophyll biosynthetic genes such as AtDVR, AtPORA, AtPORB, AtPORC, and AtCAO. Finally, the targets of VcSBPs were computationally identified in blueberry, and the Y1H assay showed that VcSBP13a could physically bind to the promoter region of the chlorophyll-associated gene VcLHCB1. Our findings provided an overall framework for individually understanding the characteristics and functions of the SBP family in blueberry.